To See or Not to See: Juridification and Challenges for Teachers in Enacting Policies on Degrading Treatment in Sweden. Issue 6 (19th September 2021) - Lindgren, Joakim; Hult, Agneta; Carlbaum, Sara; Segerholm, Christina
ABSTRACT: This article examines the juridification of education in Sweden with a particular focus on changes in the legal regulation of schools' measures to combat degrading treatment. In Swedish schools, any degrading treatment must be reported to the head teacher who, in turn, has an obligation to report it to the governing body. Based on interviews with municipal officials, school leaders, teachers and other school staff in seven schools in two municipalities, we describe and analyse how expanding bureaucratic layers of formalisation and documentation, as well as insecurity and pressures from external accountability, have transformed pedagogical challenges in terms of what teachers see and how they act on what they see.